Pengaruh Penggunaan Media Sosial Facebook dan Literasi Kewirausahaan Terhadap Motivasi Berwirausaha Dengan Efikasi Diri Sebagai Variabel Intervening - Kusuma Wardani; Ardiansyah japlani; Nani Septiana (Jurnal Manajemen DIVERSIFIKASI, 2026)
Population growth in Indonesia, according to the latest Central Statistics Agency (BPS) data, has now reached 278.69 million people by mid-2023. Based on Trading Economy data, Indonesia is the country with the second highest unemployment rate in Southeast Asia this year. It was recorded that the domestic unemployment rate reached 5.45% in February 2023. Unemployment is a major problem, especially in developing countries like Indonesia with high population growth rates. In fact, the high population growth in Indonesia is not balanced with the growth in employment opportunities or the availability of jobs in society. The method used in this research is quantitative, the data collection technique is through distributing questionnaires. The sample for this research is 76 FEB Muhammadiyah University Metro students, Class of 2020. Data was collected using a questionnaire and data analysis using validity test, reliability test, normality test, linearity test, homogeneity test, multiple linear regression analysis, t test, f test, determinant coefficient test (R2) and using SPSS 26. The results of this study show that There is a positive and significant influence of the use of Facebook social media and entrepreneurial literacy on entrepreneurial motivation. There is a positive and significant influence of the use of Facebook social media and entrepreneurial literacy on self-efficacy. There is a positive and significant influence of the use of Facebook social media and entrepreneurial literacy on entrepreneurial motivation with self-efficacy. as an intervening variable